Activation of TRPV1 and TRPM8 Channels in the Larynx and Associated Laryngopharyngeal Regions Facilitates the Swallowing Reflex - Hossain, Mohammad Zakir; Ando, Hiroshi; Unno, Shumpei; Masuda, Yuji; Kitagawa, Junichi (International journal of molecular sciences, 2018)
The larynx and associated laryngopharyngeal regions are innervated by the superior laryngeal nerve (SLN) and are highly reflexogenic. Transient receptor potential (TRP) channels have recently been detected in SLN innervated regions; however, their involvement in the swallowing reflex has not been fully elucidated. Here, we explore the contribution of two TRP channels, TRPV1 and TRPM8, located in SLN-innervated regions to the swallowing reflex. Immunohistochemistry identified TRPV1 and TRPM8 on cell bodies of SLN afferents located in the nodose-petrosal-jugular ganglionic complex. The majority of TRPV1 and TRPM8 immunoreactivity was located on unmyelinated neurons. Topical application of different concentrations of TRPV1 and TRPM8 agonists modulated SLN activity. Application of the agonists evoked a significantly greater number of swallowing reflexes compared with the number evoked by distilled water. The interval between the reflexes evoked by the agonists was shorter than that produced by distilled water. Prior topical application of respective TRPV1 or TRPM8 antagonists significantly reduced the number of agonist-evoked reflexes. The findings suggest that the activation of TRPV1 and TRPM8 channels present in the swallowing-related regions can facilitate the evoking of swallowing reflex. Targeting the TRP channels could be a potential therapeutic strategy for the management of dysphagia.